KEANEKARAGAMAN JENIS TUMBUHAN BERKAYU DI SITUS BUDAYA EYANG DALEM CAGEUR KABUPATEN KUNINGAN - Fahmi, Raizal; Saepuloh, Asep (Journal of Forestry And Environment, 2023)
This research aims to identify and document the diversity of woody plant species at the Eyang Dalem Cageur Cultural Site, Kuningan Regency. The research method involves field surveys to record the types of woody plants present, as well as data analysis to evaluate the level of diversity and distribution of species. The method used in this research is the sampling method, based on the results of the analysis of the diversity of woody plant species at the Eyang Dalem Cageur Site, Cageur Village, Darma District, Kuningan Regency, 18 types of woody plants with a total of 691 individuals from seedling level to tree level were identified. The type of plant that has an Important Value Index (INP) that dominates at the seedling level is rasamala (Altingia excelsa) with an INP of 84%, at the sapling and pole level the INP is dominated by burahol (Stelechocarpus burahol) with an INP of 69% and 118% respectively. while at tree level it is dominated by kiara (Ficus sp) with an INP of 60%. This information can be the basis for conservation and preservation of biodiversity at the Eyang Dalem Cageur Cultural Site and provide insight into the relationship between plant diversity and local cultural heritage. This research can support environmental conservation efforts and develop policies that maintain cultural and ecological values in Kuningan RegencyPenelitian ini bertujuan untuk mengidentifikasi dan mendokumentasikan keanekaragaman jenis tumbuhan berkayu di Situs Budaya Eyang Dalem Cageur, Kabupaten Kuningan. Metode penelitian melibatkan survei lapangan untuk mencatat jenis-jenis tumbuhan berkayu yang ada, serta analisis data untuk mengevaluasi tingkat keberagaman dan distribusi spesies. Metode yang digunakan dalam penelitian ini yaitu metode sampling, berdasarkan hasil analisis keanekeragaman jenis tumbuhan berkayu di Situs Eyang Dalem Cageur Desa Cageur, Kecamtan Darma, Kabupaten Kuningan teridentifikasi 18 jenis tumbuhan berkayu dengan jumlah 691 individu dari tingkat semai samapi tingkat pohon. Jenis tumbuhan yang mempunyai Indeks Nilai Penting (INP) yang mendominasi pada tingkat semai adalah rasamala (Altingia excelsa) dengan INP 84%,pada tingkat pancang dan tiang INP didominasi oleh burahol (Stelechocarpus burahol) dengan masing-masing INP 69% dan 118%, sedangkan pada tingkat pohon didominasi oleh kiara (Ficus sp) dengan INP 60%. Informasi ini dapat menjadi dasar untuk konservasi dan pelestarian keanekaragaman hayati di Situs Budaya Eyang Dalem Cageur serta memberikan wawasan tentang hubungan antara keanekaragaman tumbuhan dan warisan budaya lokal. Penelitian ini dapat mendukung upaya pelestarian lingkungan dan pengembangan kebijakan yang mempertahankan nilai-nilai budaya dan ekologis di Kabupaten Kuningan